Full sequencing and haplotype analysis of MAPT in Parkinson's disease and rapid eye movement sleep behavior disorder. Issue 6 (14th May 2018) - Li, Jiao; Ruskey, Jennifer A.; Arnulf, Isabelle; Dauvilliers, Yves; Hu, Michele T.M.; Högl, Birgit; Leblond, Claire S.; Zhou, Sirui; Ambalavanan, Amirthagowri; Ross, Jay P.; Bourassa, Cynthia V.; Spiegelman, Dan; et al.
ABSTRACT: Background: MAPT haplotypes are associated with PD, but their association with rapid eye movement sleep behavior disorder is unclear. Objective: To study the role of MAPT variants in rapid eye movement sleep behavior disorder. Methods: Two cohorts were included: (A) PD (n = 600), rapid eye movement sleep behavior disorder (n = 613) patients, and controls (n = 981); (B) dementia with Lewy bodies patients with rapid eye movement sleep behavior disorder (n = 271) and controls (n = 950). MAPT ‐associated variants and the entire coding sequence of MAPT were analyzed. Age‐, sex‐, and ethnicity‐adjusted analyses were performed to examine the association between MAPT, PD, and rapid eye movement sleep behavior disorder. Results: MAPT‐ H2 variants were associated with PD (odds ratios: 0.62‐0.65; P = 0.010‐0.019), but not with rapid eye movement sleep behavior disorder. In PD, the H1 haplotype odds ratio was 1.60 (95% confidence interval: 1.12‐2.28; P = 0.009), and the H2 odds ratio was 0.68 (95% confidence interval: 0.48‐0.96; P = 0.03). The H2/H1 haplotypes were not associated with rapid eye movement sleep behavior disorder. Conclusions: Our results confirm the protective effect of the MAPT ‐H2 haplotype in PD, and define its components. Furthermore, our results suggest that MAPT does not play a major role in rapid eye movement sleep behavior disorder, emphasizing different genetic background than in PD in this locus. © 2018 International Parkinson and Movement Disorder Society